2005
DOI: 10.1128/ec.4.4.733-741.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Major Repeat Sequence on Chromosome Loss in Candida albicans

Abstract: The major repeat sequence (MRS) is found at least once on all but one chromosome in Candida albicans, but as yet it has no known relation to the phenotype. The MRS affects karyotypic variation by serving as a hot spot for chromosome translocation and by expanding and contracting internal repeats, thereby changing chromosome length. Thus, MRSs on different chromosomes and those on chromosome homologues can differ in size. We proposed that the MRS's unique repeat structure and, more specifically, the size of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 37 publications
2
35
1
Order By: Relevance
“…The MRS remains a tantalizing structure within the genome of C. albicans; it has interesting connections to essential functions and chromosome dynamics and yet seems to be dispensable to chromosome 3 (naturally) and chromosome 5 (deleted in Lephart et al 2005). We have now shown that the MRS on chromosome 5 does not enhance mitotic recombination under standard in vitro growth conditions and rather may slightly inhibit mitotic recombination.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The MRS remains a tantalizing structure within the genome of C. albicans; it has interesting connections to essential functions and chromosome dynamics and yet seems to be dispensable to chromosome 3 (naturally) and chromosome 5 (deleted in Lephart et al 2005). We have now shown that the MRS on chromosome 5 does not enhance mitotic recombination under standard in vitro growth conditions and rather may slightly inhibit mitotic recombination.…”
Section: Discussionmentioning
confidence: 68%
“…The loss of a recombinant chromosome would introduce a partial hemizygosity for two separate chromosomes and thus potentially a new phenotype unattainable by the loss of a nonrecombinant homolog. Interestingly, the size of an MRS has also been shown to affect the frequency of chromosome nondisjunction (Lephart et al 2005); thus this repeated sequence may be involved in the regulation of both translocation and nondisjunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the genome and population processes underlying observed variation in host populations is not well understood. Appreciable rates of mitotic recombination estimated at specific genome regions (Lephart et al 2005;Lephart and Magee 2006) and in repetitive regions (Zhang et al 2003) have been evaluated primarily from in vitro cultures. Chromosomal variation as well as point mutations accumulate rapidly in populations evolving resistance to azole antifungal drugs (Selmecki et al 2006;Coste et al 2007), and in a few cases, the evolution of a pathogen within the same individual has been studied over the time course of antifungal drug treatment (Lopez-Ribot et al 1998;Marr et al 1998;Coste et al 2007;Selmecki et al 2008).…”
mentioning
confidence: 99%
“…Clinical studies reveal the accumulation of variations in host-associated populations, but rates of mitotic recombination at specific genome regions have been evaluated primarily from in vitro studies (Lephart et al 2005). High chromosomal instability in C. albicans has already been observed during growth in rich medium (Rustchenko 2007), but LOH is also widespread in natural isolates (Diogo et al 2009).…”
Section: Rapid Acquisition Of Genomic Modifications In Stressful Envimentioning
confidence: 99%